2014
DOI: 10.13005/bbra/1410
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioethanol from Papaya and Pineapple Wastes using Marine Associated Microorganisms

Abstract: Rapid increase in energy consumption and depletion of fossil fuel has lead to an extensive research in the field of alternative fuel. In this context, bioethanol has been reported as an alternative fuel because it is renewable, non toxic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, it has been shown that 25% of ethanol is required to inactivate Enterococcus faecalis effectively [65]. Natural fruit peel fermentation produces a low concentration of ethanol [66] of merely 5.4% to 13% at best, with the addition of dry yeast [67,68]. As this potential confounding factor is considered to be insignificant in previous studies, the alcohol concentration was hence not measured in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been shown that 25% of ethanol is required to inactivate Enterococcus faecalis effectively [65]. Natural fruit peel fermentation produces a low concentration of ethanol [66] of merely 5.4% to 13% at best, with the addition of dry yeast [67,68]. As this potential confounding factor is considered to be insignificant in previous studies, the alcohol concentration was hence not measured in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…The fermentation process was a monoglucose hydrolysis reaction to Ethanol (C2H5OH) synthesis [5], [18], [20]. Banana (Musa acuminata balbisiana) peel had a carbohydrates content of 1-20 g/ 100 g as glucose resources, thus bioethanol producing [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Yeast (Saccharomyces cerevisae) could be gotten easily, it obtained hydrolysis enzyme to convert carbohydrate to bioethanol in water solvent effectively [18,19]. In this research, Banana peel pulp was fermented by yeast solution.…”
Section: Introductionmentioning
confidence: 99%
“…Byproducts of food processing plant represent a major disposal problem for the industry concerned, but they are also promising sources of biomaterials. These biomaterials can be used as substrates for bioethanol production [4].…”
Section: Food Wastementioning
confidence: 99%